Patients' views of routine quality of life assessment following a diagnosis of early-stage non-small cell lung cancer. (23rd August 2020) - Pompili, Cecilia; Boele, Florien; Absolom, Kate; Holch, Patricia; Clayton, Beverly; Smyllie, Emma; Franks, Kevin; Velikova, Galina
Abstract: OBJECTIVES: There is an increasing interest in the quality of life (QoL) evaluation following video-assisted thoracoscopic anatomical lung resection or stereotactic ablative body radiotherapy for early-stage non-small-cell lung cancer (NSCLC). A qualitative interview study was conducted to gain insight into the optimal methods of assessing and discussing QoL in clinical practice. METHODS: A prospective observational longitudinal study of patients with early-stage NSCLC was conducted where repeated QoL measures were administered either online or on paper. A subset of participants was invited for qualitative interviews after the 6-month assessment or at the end of the study. The semi-structured interviews were transcribed verbatim and thematically analysed. RESULTS: Twenty-three patients were interviewed. Generally, patients were content with recruitment and data collection procedures. Most opted to complete the assessments on paper instead of online; this choice was influenced by the level of technology literacy. Some found the questionnaires too generic to reflect their experiences. Barriers to questionnaire completion were mostly practical, and many acknowledged benefits of QoL assessment including allowing them to express problems and health issues, and following changes over time. Generally, participants would like to discuss QoL results during clinical consultations, but reported this rarely happened. CONCLUSIONS: Lung cancer patient interviews confirm the acceptability of repeated QoL assessments, but online data capture is limited. Patients highlight the importance of discussing QoL aspects with their clinical team. Future strategies are needed to optimize the routine collection of patient-reported outcomes in clinical practice.